Recent progress of sulfur cathodes and other components for flexible lithium–sulfur batteries. (November 2022) - He, Y.; Bi, S.; Jiang, C.; Song, J.
Abstract: With the continuous development of flexible electronic devices, conventional energy storage equipment can hardly meet the demand. Flexible energy storage equipment is gradually coming into the vision of researchers, among which, flexible lithium-sulfur (Li–S) batteries have become the most promising energy storage devices due to their high energy density and theoretical specific capacity. There have been several urgent issues that have stymied the commercialization of this high-energy-density battery. In recent years, some excellent progress has been made on these issues. This paper reviews the current status of research on the cathode as well as other components of flexible Li–S batteries in recent years and identifies several key factors that have constrained the development.